2018
DOI: 10.1111/apps.12146
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Organisational Citizenship Behaviour: A Moderated Mediation Model of Leader‐Member‐Exchange and Subordinates' Gender

Abstract: Transformational leadership (TL) enhances follower Organizational Citizenship Behavior (OCB) as mediated by leader‐member exchange (LMX). However, the strength of the positive associations among TL, LMX and OCB is subject to significant variability. Accordingly, we draw on several theories (self‐identity, role congruency, self‐concept, and social exchange) to propose that followers' gender moderates the relationships between all three of these variables. We argue differences in societal expectations and/or und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 86 publications
5
34
0
3
Order By: Relevance
“…About 30% of teams were comprised solely of men, while the remainder had one or more female members; there were no women-only leadership teams. In light of recent findings in this context (Hackett et al, 2018), future studies should examine whether the gender composition of teams may influence the mediation effect observed here.…”
Section: Limitations and Future Directionsmentioning
confidence: 85%
“…About 30% of teams were comprised solely of men, while the remainder had one or more female members; there were no women-only leadership teams. In light of recent findings in this context (Hackett et al, 2018), future studies should examine whether the gender composition of teams may influence the mediation effect observed here.…”
Section: Limitations and Future Directionsmentioning
confidence: 85%
“…Thus, the individuals will provide better assistance to their colleagues in organizational social networks. Additionally, if employees have higher quality relation with their supervisorss, the employees will obtain better work opportunity, flexibility, and autonomy (Hackett et al, 2018). These benefits can fulfill individuals' need or desire (Sparrowe & Liden, 1997) that satisfy them.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Wang et al (2017) found that LMX has positive correlation with employees OCB in hospitality industry. The result of research Hackett et al (2018) it shows that LMX has significantly positive correlation with OCB. Based on theory and the findings, it can be concluded that the more an individual experiences a positive relation with his supervisor, namely high LMX.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 92%
“…Individu dengan LMX tinggi akan lebih mudah memperoleh informasi dan sumber daya penting dari atasannya, sehingga individu tersebut lebih dapat memberikan bantuannya kepada teman-teman dalam jejaring sosialnya di organisasi. Lebih lanjut, jika karyawan semakin memiliki hubungan kualitas yang tinggi dengan atasannya, maka karyawan tersebut akan semakin memiliki kesempatan karir, fleksibilitas, dan otonomi (Hackett et al, 2018). Benefit ini bisa membuat individu terpenuhi kebutuhan/keingginannya (Sparrowe dan Liden, 1997) yang membuat ia puas.…”
Section: Hasil Pengujian Hipotesisunclassified